Optimalisasi Desain Pencahayaan Alami Tipologi Ruang Kelas Gedung GKB UM dengan Analisis DIALUX EVO - Dewi, Cynthia Permata; Ariestadi, Dian; Sari, Astri Anindya (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2023)
Visual comfort is an important aspect of teaching and learning activities. This study used simulation with DIALux evo 9.1 at the Joint Lecture Building (GKB) State University of Malang. Data analysis uses a quantitative descriptive approach. Natural lighting simulation is carried out to get an idea of natural lighting and its effects. The results showed that the average intensity of room lighting was above the lighting standard. The highest intensity occurs at 12:00, while the lowest is at 16:00. The level of visual comfort due to natural lighting is not optimal. Very high lighting intensity results in glare effect on the transparent wall side of the room, while the inner side is below the room lighting standard. The influence of architectural and façade design that affects the optimization of natural lighting is: building orientation, the use of transparent walls full of CW (curtain wall) construction, minimizing the use of horizontal shading, by tending to use vertical shading-fins, and making transparent material selection.